The flat [videorecording (DVD)] = ha-Dirah [romanized form] - Goldfinger, Arnon, 1963-; Goldfinger, Arnon, 1963-; Goldfinger, Arnon, 1963-; Goldfinger, Arnon, 1963- (IFC Films : MPI Home Video, 2013)
"[F]ilmmaker Arnon Goldfinger travels to Tel Aviv to clean out the apartment of his recently-deceased German-born Jewish grandmother. ... Goldfinger begins an unsettling journey into his family's history ... and discovers that knowing the truth can be a terrible burden. ... The Flat is a real-life suspense story about how the past can return to haunt the present."--Container.